Improving Financial Literacy of Msmes Through Simple Financial Management Training in Kemang Village, Bojong Picung District, Cianjur Regency - Dodi Siswanto; Yogi Sahrul Danda; Risya Fierda Fhadillah; Fitri Nur Fauziah; Nuryani Aulia Eka Putri; Imel Meilani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Training on Basic Financial Management for Micro, Small, and Medium Enterprises (MSMEs) in Kemang Village, Bojongpicung Subdistrict, Cianjur Regency was carried out in response to the community’s lack of understanding. The goal of this financial literacy training is to improve knowledge on financial record-keeping, budget planning, and the separation of business and personal finances. Many business actors still operate without a clear and organized financial system, making it difficult for them to assess business growth or make data-based decisions. This activity was designed to be simple and easy to understand, so it could be immediately applied. The method used was a training session lasting approximately 4 hours. Participants consisted of 30 individuals from various backgrounds, including MSME actors, BUMDes Wanamukti administrators, village officials, and community leaders. The training materials covered topics such as the importance of transaction recording, basic financial management, and daily cash flow tracking. Evaluation was conducted interactively through group discussions, hands-on practice, and Q&A sessions using Google Forms. The results showed an increase in participants' understanding of financial reports. Additionally, there was a mutual agreement among participants to begin routinely recording their business finances. This activity is expected to mark a positive beginning in forming sound financial habits and encouraging the development of a more organized, structured, and sustainable MSME financial system at the village level. The outcome showed that the financial literacy index initially stood at around 66,73% and rose to 93% after the training was conducted.money system at the village level.